Flame-retardant polymer electrolyte for lithium ion battery as well as preparation method and application of flame-retardant polymer electrolyte
The molecular structure of the polymer electrolyte is optimized through copolymerization modification technology, which solves the problems of insufficient flame retardant performance and ionic conductivity, and significantly improves the safety and cycle stability of lithium batteries.
Patent Information
- Application Number
- CN202411864012.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-12-18
AI Technical Summary
The existing polymer electrolytes have shortcomings in flame retardant properties and ionic conductivity, resulting in limited safety and cycling stability of lithium batteries.
The molecular structure of the polymer electrolyte is optimized through copolymerization modification technology, and appropriate functional groups are introduced to improve its flame retardant performance and conductivity.
While ensuring the flame retardant effect with excellent electrolytes of polymer, it effectively improves its ion conductivity, thereby improving the safety and cycle stability of lithium batteries.
Smart Images

Figure CN119340470A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of flame retardant polymer electrolytes, and in particular to a flame retardant polymer electrolyte for lithium ion batteries and a preparation method and application thereof. Background Art
[0002] Since its introduction in the 1990s, lithium-ion batteries have been widely used in consumer electronics, electric vehicles, energy storage systems, and other fields due to their high energy density, long service life, and environmentally friendly characteristics. With the continuous growth of market demand, especially electric vehicles and portable electronic products have put forward higher requirements for battery performance, how to further improve the safety, energy density, and cycle stability of lithium-ion batteries has become a hot topic in current research. However, although lithium batteries play an important role in various fields, their safety issues are still one of the key factors restricting their widespread application. Liquid electrolytes are the core components of lithium batteries. Traditional liquid electrolytes are mainly composed of organic solvents and lithium salts. Commonly used organic solvents such as carbonates and ethers have good solubility, but their volatility and flammability, especially under extreme conditions such as high temperature or short circuit, often cause thermal runaway of the battery, and even cause the battery to catch fire or explode in severe cases, thus posing a great threat to the safety of the battery. Therefore, how to reduce the combustible components in the battery and improve the thermal stability of the battery has become a technical problem that needs to be solved urgently.
[0003] In response to the above safety issues, polymer electrolytes have gradually attracted widespread attention as alternative materials for liquid electrolytes in recent years. Polymer lithium batteries can effectively avoid the flammability and volatility of liquid electrolytes by replacing traditional liquid electrolytes with polymer electrolytes, thereby improving the safety performance of batteries. The application of polymer electrolytes in lithium batteries can eliminate the safety hazards brought by traditional liquid organic electrolytes, especially in the case of thermal runaway or internal short circuit of the battery, it can avoid the combustion of electrolytes and significantly improve the safety of batteries. However, the widespread application of polymer electrolytes still faces many challenges. First, the ionic conductivity of polymer electrolytes is generally poor. Because the ionic conduction mechanism of polymer electrolytes is different from that of liquid electrolytes, the resistance at the solid-solid interface is large, and the interface impedance between the electrode and the polymer electrolyte is high, resulting in low conductivity of the battery, which limits the energy output and working efficiency of the battery. Secondly, the mechanical strength and thermal stability of polymer electrolytes are still insufficient, especially in high temperature environments, polymer electrolytes may decompose or become structurally unstable, thus affecting the long-term stability and safety of the battery. Therefore, how to improve the conductivity of polymer electrolytes while ensuring their safety and stability is the main topic in the current research field.
[0004] At present, researchers have tried to improve the performance of polymer electrolytes by doping. The doping method introduces fillers or dopants into polymer electrolytes in order to improve their ionic conductivity or thermal stability. However, this method often faces the problem of incompatibility between fillers and polymer matrices, resulting in interface separation of polymer electrolytes, which in turn increases the internal resistance of the battery and reduces battery performance.
[0005] Therefore, how to further improve the flame retardancy of polymer electrolytes without sacrificing conductivity has become a major problem in current technology. In addition, the existing technology still lacks research on the thermal stability and cycle performance of polymer electrolytes at high temperatures. Especially in practical applications, the performance degradation problem of polymer electrolytes at high temperatures is still very prominent. Therefore, it is particularly urgent and necessary to find a technical solution that can improve the ionic conductivity of polymer electrolytes while ensuring their good thermal stability and flame retardancy.
[0006] The present invention aims to solve the deficiencies of polymer electrolytes in the prior art in terms of flame retardancy and ionic conductivity, and to provide a polymer electrolyte with high flame retardancy and conductivity. By optimizing the molecular structure of the polymer electrolyte through a copolymerization method and introducing appropriate functional groups, the present invention can effectively improve the ionic conductivity of the polymer electrolyte while ensuring its excellent flame retardant effect, thereby improving the safety and cycle stability of lithium batteries. This technological innovation not only solves the contradiction between the conductivity and flame retardancy of existing polymer electrolytes, but also provides new ideas and solutions for the promotion of polymer electrolytes in practical applications. Summary of the invention
[0007] In order to achieve the above-mentioned purpose of the invention and to solve the above-mentioned technical problems, the present invention provides a flame-retardant polymer electrolyte and a preparation method thereof using copolymerization modification technology, thereby preparing a polymer electrolyte with high efficiency flame retardancy and electrical conductivity.
[0008] The present invention provides a method for preparing a flame-retardant polymer electrolyte for a lithium-ion battery, wherein the steps of the preparation method are as follows: (1) dissolving acrylonitrile and vinyl acetate in deionized water to obtain solution A, and adding sodium dodecyl sulfate and potassium persulfate to the solution A under a nitrogen atmosphere to obtain solution B; (2) soaking the solution B in a diethylenetriamine solution to obtain a solution C; (3) Filtering the solution C, washing it, and drying it to obtain the product D; (4) adding bacterial cellulose and lithium bis(trifluoromethanesulfonyl)imide to the product D, and dissolving the product D in N-methylpyrrolidone to obtain a solution E; (5) The solution E is poured into a mold and heated to evaporate the solvent to obtain a flame retardant polymer electrolyte AP (AN-VAC).
[0009] The reaction formula of the flame retardant polymer electrolyte is as follows: ; Preferably, the specific process of step (1) corresponding to every 8-10 g of acrylonitrile is as follows: 8-10 g of acrylonitrile and 1-1.5 g of vinyl acetate are dissolved in 30-35 mL of deionized water to obtain solution A; 0.2-0.3 g of sodium dodecyl sulfate and 0.3-0.4 g of potassium persulfate are slowly added to solution A under nitrogen conditions to obtain a homogeneous solution B.
[0010] Preferably, the specific steps of step (2) are: soaking the homogeneous solution B in 40-50 mL of diethylenetriamine solution under a nitrogen atmosphere to obtain solution C; Preferably, the specific steps of step (3) are: after filtering the solution C, washing it with deionized water and ethanol in sequence to obtain a white solid product; after heating and drying the white solid product, obtaining product D, the heating temperature is 60-80°C.
[0011] Preferably, the specific steps of step (4) are: 1-1.2 g of product D, 3-4 g of bacterial cellulose with a mass concentration of 0.4% and 0.3-0.32 g of lithium bis(trifluoromethanesulfonyl)imide are mixed and dissolved in 12-15 ml of N-methylpyrrolidone to obtain solution E.
[0012] Preferably, the solution E is poured onto a polytetrafluoroethylene template and heated at 60-80° C. for 5-7 h to obtain a flame retardant polymer electrolyte AP (AN-VAC).
[0013] Preferably, in step (1), the concentration of acrylonitrile is 95-99% w / v, and the concentration of vinyl acetate is 95-99% w / v; in step (2), the concentration of N-methylpyrrolidone is 95-99% w / v.
[0014] The present invention also provides a flame retardant polymer electrolyte for a lithium ion battery, and the flame retardant polymer electrolyte is prepared by the above-mentioned preparation method.
[0015] The present invention also provides a method for preparing a flame-retardant polymer electrolyte lithium-ion battery, wherein the lithium battery comprises a lithium half-cell or a lithium full-cell.
[0016] The lithium half-cell preparation method comprises the following steps: (A) lithium iron phosphate: carbon black: polyvinylidene fluoride are dispersed in a ratio of 8:1:1 using N-methylpyrrolidone, ground evenly, and then coated on aluminum foil using a scraper, and dried to obtain a lithium iron phosphate electrode; (B) A lithium battery was prepared using a metallic lithium sheet as the negative electrode, a lithium iron phosphate sheet as the positive electrode, and AP (AN-VAC) as a polymer flame-retardant electrolyte.
[0017] The lithium full battery preparation method comprises the following steps: (a) lithium iron phosphate: carbon black: polyvinylidene fluoride are dispersed in a ratio of 8:1:1 using N-methylpyrrolidone, ground evenly, and then coated on aluminum foil using a scraper, and dried to obtain a lithium iron phosphate electrode; (b) artificial graphite: carbon black: polyvinylidene fluoride is dispersed in N-methylpyrrolidone in a ratio of 8:1:1, ground evenly, coated on aluminum foil with a scraper, and dried to obtain a graphite electrode; (c) A lithium battery was prepared using graphite as the negative electrode, lithium iron phosphate as the positive electrode, and AP (AN-VAC) as the polymer flame-retardant electrolyte.
[0018] The AP (AN-VAC) is prepared by the above-mentioned preparation method.
[0019] The present invention also provides a flame retardant polymer electrolyte lithium ion battery, and the lithium ion battery is prepared by the above-mentioned preparation method.
[0020] The beneficial effects brought by the technical solution provided by the present invention are: The present invention adopts economical and practical PAN as the main body, and adopts copolymerization modification to synthesize AP (AN-VAC), so as to prepare polymer electrolyte AP (AN-VAC) with excellent flame retardant effect. The copolymerization modification technology not only enables AP (AN-VAC) to eliminate free radicals released by PAN combustion, so as to play a flame retardant role under high temperature, but also has a significant effect.
[0021] Secondly, AP (AN-VAC) can effectively improve the safety performance of polymer electrolytes through -NH2 under thermal runaway conditions, control the combustion reaction of combustibles, promote the movement of polymer electrolyte matrix chains and C=O functional groups as lithium ion migration sites to improve electron transfer and ion transfer, and form hydrogen bonds through its own functional groups to improve the mechanical properties of the polymer and inhibit the growth of lithium dendrites, thereby improving the cycle performance of lithium batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 : Infrared image of AP(AN-VAC)1 obtained in Example 1; Figure 2: Scanning electron microscopy image of AP(AN-VAC)1 obtained in Example 1; Figure 3 : Thermogravimetric diagram of AP(AN-VAC)1 obtained in Example 1; Figure 4 : Thermogravimetric diagram of PAN obtained in Comparative Example 1; Figure 5 : Thermogravimetric diagram of P(AN-VAC) obtained in Comparative Example 2; Figure 6 : Experimental graph of limiting oxygen index of Example 1 and control groups 1 and 2; Figure 7 : Nyquist diagram of the AP(AN-VAC)1 half-cell obtained in Example 1; Figure 8 : Nyquist plot of the PAN half-cell obtained in Comparative Example 1; Fig. 9 : Nyquist diagram of the P(AN-VAC) half-cell obtained in Comparative Example 2; Fig.10 : The AP(AN-VAC)1 half-cell obtained in Example 1 is cycled at different rates - specific capacity diagram; Fig.11 : Cycle-specific capacity diagram of the PAN half-cell obtained in Comparative Example 1 at different rates; Fig.12 : Cycle-specific capacity diagram of the P(AN-VAC) half-cell obtained in Comparative Example 2 at different rates; Fig.13 : The AP(AN-VAC)2 half-cell obtained in Example 2 is cycled at different rates - specific capacity diagram; Fig.14 : The AP(AN-VAC)3 half-cell obtained in Example 3 is cycled at different rates - specific capacity diagram; Fig.15 : The AP(AN-VAC)4 half-cell obtained in Example 4 has a cycle-specific capacity diagram at different rates; Fig.16 : The AP(AN-VAC)5 half-cell obtained in Example 5 is cycled at different rates - specific capacity diagram; Fig.17 : The AP(AN-VAC)6 half-cell obtained in Example 6 has a cycle-specific capacity diagram at different rates; Fig.18 : Cycle-efficiency & specific capacity test of the AP(AN-VAC)7 full battery obtained in Example 7; Fig.19 : Cycle-efficiency & specific capacity test of the PAN full battery obtained in Comparative Example 1; Fig. 20 : Cycle-efficiency & specific capacity test of the P(AN-VAC) full battery obtained in Comparative Example 2; Fig.21 : The AP(AN-VAC)8 half-cell obtained in Example 8 is cycled at different rates - specific capacity diagram; Fig. 22 : Cycle-specific capacity diagram of the AP(AN-VAC)9 half-cell obtained in Example 9 at different rates. DETAILED DESCRIPTION
[0023] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. Of course, the specific embodiments described here are only used to explain the present invention and are not used to limit the present invention.
[0024] Example 1: Changing the synthesis temperature of AP(AN-VAC)1 to 60°C (1) Synthesis of AP(AN-VAC)1 In 60 o Synthesis of AP(AN-VAC)1 under C conditions 1. Dissolve 9 g acrylonitrile and 1 g vinyl acetate in 30 mL deionized water to obtain solution A. Slowly add 0.2 g sodium dodecyl sulfate and 0.3 g potassium persulfate to solution A at room temperature to obtain a homogeneous solution B.
[0025] 2. The homogeneous solution B was immersed in 40 mL of diethylenetriamine solution under a nitrogen atmosphere to obtain a solution C; the solution C was filtered and washed with deionized water and ethanol in sequence to obtain a white solid product; the white solid product was heated for 60 o After drying C, product D was obtained.
[0026] (2) Preparation of organic polymer electrolytes 1. Mix 1 g of product D, 3 g of bacterial cellulose with a mass concentration of 0.4% and 0.3 g of lithium bis(trifluoromethanesulfonyl)imide, and dissolve them in 15 ml of N-methylpyrrolidone (NMP) to obtain solution E; The solution E was poured onto a polytetrafluoroethylene template at 60 o C for 6 h to obtain the flame-retardant polymer electrolyte AP(AN-VAC)1; The concentration of acrylonitrile is 95% w / v, the concentration of vinyl acetate is 95% w / v, and the concentration of N-methylpyrrolidone is 95% w / v; 2. The flame-retardant polymer electrolyte AP(AN-VAC)1 was prepared into a disc with a diameter of 16 mm; (3) Preparation of positive electrode: Disperse lithium iron phosphate (LFP): carbon black: PVDF = 8:1:1 with N-methylpyrrolidone, grind evenly, apply on aluminum foil with a scraper, and dry to obtain lithium iron phosphate electrode; (4) Preparation of lithium half-cell: Use lithium metal sheet as negative electrode, lithium iron phosphate electrode as positive electrode, and AP (AN-VAC) 1 as polymer electrolyte to prepare 2032 button cell; The graphite used is: CLUDE, artificial graphite powder SAG20N for lithium batteries; The carbon black used is: Kelude, conductive silicate carbon black for lithium battery positive electrode.
[0027] Example 2: Changing the AP (AN-VAC) synthesis temperature to 70 °C (1) Synthesis of AP(AN-VAC)2 Synthesis of AP(AN-VAC)2 at 70 ℃ 1. Dissolve 9 g acrylonitrile and 1 g vinyl acetate in 30 mL deionized water to obtain solution A. Slowly add 0.2 g sodium dodecyl sulfate and 0.3 g potassium persulfate to solution A at room temperature to obtain a homogeneous solution B.
[0028] 2. The homogeneous solution B was immersed in 40 mL of diethylenetriamine solution under a nitrogen atmosphere to obtain a solution C; the solution C was filtered and washed with deionized water and ethanol in sequence to obtain a white solid product; the white solid product was heated at 70 o After drying C, product D was obtained.
[0029] (2) Preparation of organic polymer electrolytes 1. Mix 1 g of product D, 3 g of bacterial cellulose with a mass concentration of 0.4% and 0.3 g of lithium bis(trifluoromethanesulfonyl)imide, and dissolve them in 15 ml of N-methylpyrrolidone (NMP) to obtain solution E; The solution E was poured onto a polytetrafluoroethylene template at 70 o C for 6 h to obtain the flame-retardant polymer electrolyte AP (AN-VAC); The concentration of acrylonitrile is 95% w / v, the concentration of vinyl acetate is 95% w / v, and the concentration of N-methylpyrrolidone is 95% w / v; 2. The obtained flame-retardant polymer electrolyte AP(AN-VAC)2 was prepared into a disc with a diameter of 16 mm; (3) Preparation of positive electrode: Disperse lithium iron phosphate (LFP): carbon black: PVDF = 8:1:1 with N-methylpyrrolidone, grind evenly, apply on aluminum foil with a scraper, and dry to obtain lithium iron phosphate electrode; (4) Preparation of lithium half-cell: Use lithium metal sheet as negative electrode, lithium iron phosphate electrode as positive electrode, and AP (AN-VAC) 2 as polymer electrolyte to prepare 2032 button cell; The graphite used is: CLUDE, artificial graphite powder SAG20N for lithium batteries; The carbon black used is: Kelude, conductive silicate carbon black for lithium battery positive electrode.
[0030] Example 3: Changing the AP (AN-VAC) synthesis temperature to 80 °C (1) Synthesis of AP(AN-VAC)3 Synthesis of AP(AN-VAC) at 80 ℃ 1. Dissolve 9 g acrylonitrile and 1 g vinyl acetate in 30 mL deionized water to obtain solution A. Slowly add 0.2 g sodium dodecyl sulfate and 0.3 g potassium persulfate to solution A at room temperature to obtain a homogeneous solution B.
[0031] 2. The homogeneous solution B was immersed in 40 mL of diethylenetriamine solution under a nitrogen atmosphere to obtain a solution C; the solution C was filtered and washed with deionized water and ethanol in sequence to obtain a white solid product; the white solid product was heated for 80 o After drying C, product D was obtained.
[0032] (2) Preparation of organic polymer electrolytes 1. Mix 1 g of product D, 3 g of bacterial cellulose with a mass concentration of 0.4% and 0.3 g of lithium bis(trifluoromethanesulfonyl)imide, and dissolve them in 15 ml of N-methylpyrrolidone (NMP) to obtain solution E; The solution E was poured onto a polytetrafluoroethylene template at 80 o C for 6 h to obtain the flame-retardant polymer electrolyte AP(AN-VAC)3; The concentration of acrylonitrile is 95% w / v, the concentration of vinyl acetate is 95% w / v, and the concentration of N-methylpyrrolidone is 95% w / v; 2. The obtained flame-retardant polymer electrolyte AP(AN-VAC)3 was prepared into a disc with a diameter of 16 mm; (3) Preparation of positive electrode: Disperse lithium iron phosphate (LFP): carbon black: PVDF = 8:1:1 with N-methylpyrrolidone, grind evenly, apply on aluminum foil with a scraper, and dry to obtain lithium iron phosphate electrode; (4) Preparation of lithium half-cell: Use lithium metal sheet as negative electrode, lithium iron phosphate electrode as positive electrode, and AP (AN-VAC) 3 as polymer electrolyte to prepare 2032 button cell; The graphite used is: CLUDE, artificial graphite powder SAG20N for lithium batteries; The carbon black used is: Kelude, conductive silicate carbon black for lithium battery positive electrode.
[0033] Example 4: The preparation process is similar to that of Example 1, except that in the preparation process of the organic polymer electrolyte, in step 1, the amount of product D added is 1.2 g to synthesize AP(AN-VAC)4.
[0034] Example 5: The preparation process is similar to that of Example 1, except that, in the preparation process of the organic polymer electrolyte, in step 1, 4 g of bacterial cellulose is added to synthesize AP(AN-VAC)5.
[0035] Example 6: The preparation process is similar to that of Example 1, except that, in the preparation process of the organic polymer electrolyte, in step 1, 12 mL of N-methylpyrrolidone is added to synthesize AP(AN-VAC)6.
[0036] Example 7: The preparation process is similar to that of Example 1, except that a full battery, a lithium full battery, is prepared; Preparation of negative electrode: artificial graphite: carbon black: PVDF = 8:1:1 is dispersed in N-methylpyrrolidone, ground evenly, and then coated on aluminum foil with a scraper, and dried to obtain a graphite electrode; Preparation of lithium full battery: Use graphite pole piece as negative electrode, lithium iron phosphate pole piece as positive electrode, and AP (AN-VAC) 1 as polymer electrolyte to prepare 2032 button battery.
[0037] Example 8: (1) Synthesis of AP(AN-VAC)8 Synthesis of AP(AN-VAC)8 at 60 ℃ 1. Dissolve 8 g acrylonitrile and 1 g vinyl acetate in 30 mL deionized water to obtain solution A. Slowly add 0.2 g sodium dodecyl sulfate and 0.3 g potassium persulfate to solution A at room temperature to obtain a homogeneous solution B.
[0038] 2. The homogeneous solution B was immersed in 40 mL of diethylenetriamine solution under a nitrogen atmosphere to obtain solution C; the solution C was filtered and washed with deionized water and ethanol in sequence to obtain a white solid product; the white solid product was heated at 60 °C and dried to obtain product D.
[0039] (2) Preparation of organic polymer electrolytes 1. Mix 1 g of product D, 3 g of bacterial cellulose with a mass concentration of 0.4% and 0.3 g of lithium bis(trifluoromethanesulfonyl)imide, and dissolve them in 12 ml of N-methylpyrrolidone (NMP) to obtain solution E; The solution E was poured onto a polytetrafluoroethylene template and heated at 60° C. for 5 h to obtain a flame retardant polymer electrolyte AP(AN-VAC)8; The concentration of acrylonitrile is 95% w / v, the concentration of vinyl acetate is 95% w / v, and the concentration of N-methylpyrrolidone is 95% w / v; 2. The obtained flame-retardant polymer electrolyte AP(AN-VAC)8 was prepared into a disc with a diameter of 16 mm; (3) Preparation of positive electrode: Disperse lithium iron phosphate (LFP): carbon black: PVDF = 8:1:1 with N-methylpyrrolidone, grind evenly, apply on aluminum foil with a scraper, and dry to obtain lithium iron phosphate electrode; (4) Preparation of lithium half-cell: Use lithium metal sheet as negative electrode, lithium iron phosphate electrode as positive electrode, and AP (AN-VAC) 8 as polymer electrolyte to prepare 2032 button cell; The graphite used is: CLUDE, artificial graphite powder SAG20N for lithium batteries; The carbon black used is: Kelude, conductive silicate carbon black for lithium battery positive electrode.
[0040] Example 9: (1) Synthesis of AP(AN-VAC) Synthesis of AP(AN-VAC)9 at 60 ℃ 1. Dissolve 10 g acrylonitrile and 1.5 g vinyl acetate in 35 mL deionized water to obtain solution A. Slowly add 0.3 g sodium dodecyl sulfate and 0.4 g potassium persulfate to solution A at room temperature to obtain a homogeneous solution B.
[0041] 2. The homogeneous solution B was immersed in 50 mL of diethylenetriamine solution under a nitrogen atmosphere to obtain solution C; the solution C was filtered and washed with deionized water and ethanol in sequence to obtain a white solid product; the white solid product was heated at 60 °C and dried to obtain product D.
[0042] (2) Preparation of organic polymer electrolytes 1. Mix 1.2 g of product D, 4 g of bacterial cellulose with a mass concentration of 0.4%, and 0.32 g of lithium bis(trifluoromethanesulfonyl)imide, and dissolve them in 15 ml of N-methylpyrrolidone (NMP) to obtain solution E; The solution E was poured onto a polytetrafluoroethylene template and heated at 60°C for 7 hours to obtain a flame retardant polymer electrolyte AP(AN-VAC)9; The concentration of acrylonitrile is 99% w / v, the concentration of vinyl acetate is 99% w / v, and the concentration of N-methylpyrrolidone is 99% w / v; 2. The obtained flame-retardant polymer electrolyte AP(AN-VAC)9 was prepared into a disc with a diameter of 16 mm; (3) Preparation of positive electrode: Disperse lithium iron phosphate (LFP): carbon black: PVDF = 8:1:1 with N-methylpyrrolidone, grind evenly, apply on aluminum foil with a scraper, and dry to obtain lithium iron phosphate electrode; (4) Preparation of lithium half-cell: Use lithium metal sheet as negative electrode, lithium iron phosphate electrode as positive electrode, and AP (AN-VAC) 9 as polymer electrolyte to prepare 2032 button cell; The graphite used is: CLUDE, artificial graphite powder SAG20N for lithium batteries; The carbon black used is: Kelude, conductive silicate carbon black for lithium battery positive electrode.
[0043] Comparative Example 1: The same preparation method as in Example 1 was used, except that PAN was used to replace the membrane formed by product D, the PAN membrane was prepared according to the method of step (2) of Example 1, the PAN membrane was used as the polymer electrolyte, and a 2032 button cell was prepared according to the method of steps (3)-(4) of Example 1.
[0044] Comparative Example 2: The same preparation method as in Example 1 was used, except that no diethylenetriamine solution was added for copolymerization modification in step (1), and the P(AN-VAC) membrane was prepared according to the method of step (2) of Example 1. The P(AN-VAC) membrane was used as the polymer electrolyte, and 2032 button cells were prepared according to the methods of steps (3)-(4) of Example 1.
[0045] Experimental test of Example 1 and Comparative Examples 1 and 2: 1. Use Fourier transform infrared spectrometer to detect the functional groups of AP(AN-VAC)1 Figure 1 shown.
[0046] from Figure 1It can be seen that AP(AN-VAC)1 was successfully synthesized with a unique absorption peak at 3200.
[0047] 2. The morphology of AP(AN-VAC)1 detected by scanning electron microscopy is as follows Figure 2 shown.
[0048] from Figure 2 It can be seen that the film is formed by heat, and the surface of the film is very uniform with few pores, which is conducive to close contact with the lithium negative electrode.
[0049] 3. Thermogravimetric test results of AP(AN-VAC)1 membrane under nitrogen conditions are as follows Figure 3 shown.
[0050] from Figure 3 It can be seen that the effect of AP(AN-VAC)1 membrane is very good and it still maintains 50% at high temperature, but the decomposition temperature of AP(AN-VAC)1 membrane is higher, proving that it has better thermal stability.
[0051] 4. Thermogravimetric test results of PAN membrane under nitrogen conditions are as follows Figure 4 As shown. Figure 4 It can be seen that the PAN film only maintained 43% under high temperature conditions.
[0052] 5. Thermogravimetric test results of P(AN-VAC) membrane under nitrogen conditions are as follows Figure 5 As shown. Figure 5 It can be seen that the P(AN-VAC) film maintains 41%, and the decomposition temperature of the P(AN-VAC) film is not as high as that of the AP(AN-VAC)1 film.
[0053] 6. The flame retardant performance test results of AP (AN-VAC) 1 film are as follows Figure 6 shown.
[0054] Figure 6 is the limiting oxygen index test result, from Figure 6 It can be seen that the limiting oxygen index of AP(AN-VAC)1 is 24%, which once again proves that the copolymerization reaction inhibits the combustion of the film.
[0055] 7. The battery performance test results of the AP(AN-VAC)1 membrane prepared in Example 1 and the PAN membrane and P(AN-VAC) membrane of the control group are as follows: Figure 7-9 shown.
[0056] AP(AN-VAC)1 film, PAN film and P(AN-VAC) film were used to assemble lithium half-cells and Nyquist tests were performed. The results are shown in Figure 7-9 As shown, from Figure 7-9It can be seen that the test interval is 10 mHZ-100 kHZ, showing the battery impedance values of 225, 350 and 300 Ω; 8. Use AP(AN-VAC)1 membrane, PAN membrane and P(AN-VAC) membrane as electrolyte, lithium sheet as negative electrode, lithium iron phosphate coating as positive electrode to assemble half-cell. Then, perform half-cell rate performance test. Charge and discharge cycles are performed at current densities of 0.2 C, 0.5 C, 1 C, 2 C, 3C and 0.2 C respectively. The cut-off voltage of the test is 2.5-4.2V. Charge and discharge cycles are performed 5 times at each rate. The results are as follows: Figure 10-12 shown.
[0057] from Figure 10-12 It can be seen that the half-cell can be stably charged and discharged at different current densities, and the specific capacity values at the beginning and the end when it returns to 0.2 C are similar, indicating that the electrochemical properties of AP(AN-VAC)1 are stable. At the maximum current density of 3C, the specific capacity reaches 123.9 mAh / g; while the specific capacity corresponding to PAN and P(AN-VAC) fluctuates greatly with the change of current density; in summary, it proves that the current density range applicable to AP(AN-VAC)1 is very excellent.
[0058] Experimental test of Example 2 and Comparative Examples 1 and 2: A half-cell was assembled using AP(AN-VAC)2 membrane, PAN membrane and P(AN-VAC) membrane as electrolyte, lithium sheet as negative electrode and lithium iron phosphate coating as positive electrode. Then the half-cell rate performance test was carried out. The charge and discharge cycles were carried out at current densities of 0.2 C, 0.5 C, 1 C, 2 C, 3 C and 0.2 C respectively. The test cut-off voltage was 2.5-4.2V. Five charge and discharge cycles were carried out at each rate. The results are shown in the figure. Figure 11-13 shown.
[0059] from Figure 11-13 It can be seen that the half-cell can be stably charged and discharged at different current densities, and the specific capacity values at the beginning and the end when it returns to 0.2 C are similar, indicating that the electrochemical properties of AP(AN-VAC)2 are stable. At the maximum current density of 3C, the specific capacity reaches 102 mAh / g; while the specific capacity corresponding to PAN and P(AN-VAC) fluctuates greatly with the change of current density; in summary, it proves that the current density range applicable to AP(AN-VAC)2 is very excellent. However, compared with AP(AN-VAC)1, its specific capacity retention rate is not as good as AP(AN-VAC)1.
[0060] Experimental test of Example 3 and Comparative Examples 1 and 2: A half-cell was assembled using AP(AN-VAC)3 membrane, PAN membrane and P(AN-VAC) membrane as electrolyte, lithium sheet as negative electrode and lithium iron phosphate coating as positive electrode. The half-cell rate performance test was then carried out. The charge and discharge cycles were carried out at current densities of 0.2 C, 0.5 C, 1 C, 2 C, 3 C and 0.2 C respectively. The test cut-off voltage was 2.5-4.2V. Five charge and discharge cycles were carried out at each rate. The results are shown in the figure. Fig.11 ,12,14 as shown.
[0061] from Fig.11 ,12,14It can be seen that the half-cell can be stably charged and discharged at different current densities, and the specific capacity values at the beginning and the end when it returns to 0.2 C are similar, indicating that the electrochemical properties of AP(AN-VAC)3 are stable. At the maximum current density of 3C, the specific capacity reaches 93.6 mAh / g; while the specific capacity corresponding to PAN and P(AN-VAC) fluctuates greatly with the change of current density; but compared with AP(AN-VAC)1, its specific capacity retention rate is not as good as AP(AN-VAC)1.
[0062] Experimental detection of Example 4 and Comparative Examples 1 and 2: A half-cell was assembled using AP(AN-VAC)4 membrane, PAN membrane and P(AN-VAC) membrane as electrolyte, lithium sheet as negative electrode and lithium iron phosphate coating as positive electrode. Then the half-cell rate performance test was carried out. The charge and discharge cycles were carried out at current densities of 0.2 C, 0.5 C, 1 C, 2 C, 3 C and 0.2 C respectively. The test cut-off voltage was 2.5-4.2V. Five charge and discharge cycles were carried out at each rate. The results are shown in the figure. Fig.11 , as shown in 12,15.
[0063] from Fig.11 ,12,15It can be seen that the half-cell can be stably charged and discharged at different current densities, and the specific capacity values at the beginning and the end when it returns to 0.2 C are similar, indicating that the electrochemical properties of AP(AN-VAC)4 are stable. At the maximum current density of 3C, the specific capacity reaches 89.4 mAh / g; while the specific capacity corresponding to PAN and P(AN-VAC) fluctuates greatly with the change of current density; but compared with AP(AN-VAC)1, its specific capacity retention rate is not as good as AP(AN-VAC)1.
[0064] Experimental test of Example 5 and Comparative Examples 1 and 2: A half-cell was assembled using AP(AN-VAC)5 membrane, PAN membrane and P(AN-VAC) membrane as electrolyte, lithium sheet as negative electrode and lithium iron phosphate coating as positive electrode. Then the half-cell rate performance test was carried out. The charge and discharge cycles were carried out at current densities of 0.2 C, 0.5 C, 1 C, 2 C, 3 C and 0.2 C respectively. The test cut-off voltage was 2.5-4.2V. Five charge and discharge cycles were carried out at each rate. The results are shown in the figure. Fig.11 ,12,16 as shown.
[0065] from Fig.11 ,12,16It can be seen that the half-cell can be stably charged and discharged at different current densities, and the specific capacity values at the beginning and the end when it returns to 0.2 C are similar, indicating that the electrochemical properties of AP(AN-VAC)5 are stable. At the maximum current density of 3C, the specific capacity reaches 101.3 mAh / g; while the specific capacity corresponding to PAN and P(AN-VAC) fluctuates greatly with the change of current density; but compared with AP(AN-VAC)1, its specific capacity retention rate is not as good as AP(AN-VAC)1.
[0066] Experimental detection of Example 6 and Comparative Examples 1 and 2: A half-cell was assembled using AP(AN-VAC)6 membrane, PAN membrane and P(AN-VAC) membrane as electrolyte, lithium sheet as negative electrode and lithium iron phosphate coating as positive electrode. Then the half-cell rate performance test was carried out. The charge and discharge cycles were carried out at current densities of 0.2 C, 0.5 C, 1 C, 2 C, 3 C and 0.2 C respectively. The cut-off voltage of the test was 2.5-4.2V. Five charge and discharge cycles were carried out at each rate. The results are shown in the figure. Fig.11 ,12,17 as shown.
[0067] from Fig.11 ,12,17It can be seen that the half-cell can be stably charged and discharged at different current densities, and the specific capacity values at the beginning and the end when it returns to 0.2 C are similar, indicating that the electrochemical properties of AP(AN-VAC)6 are stable. At the maximum current density of 3C, the specific capacity reaches 85.6 mAh / g; while the specific capacity corresponding to PAN and P(AN-VAC) fluctuates greatly with the change of current density; but compared with AP(AN-VAC)1, its specific capacity retention rate is not as good as AP(AN-VAC)1.
[0068] Example 7 Experimental detection with PAN film and P(AN-VAC): The full battery was assembled using AP(AN-VAC)1 membrane, PAN membrane and P(AN-VAC) membrane as electrolyte, graphite as negative electrode and lithium iron phosphate coating as positive electrode. The cycle-efficiency & specific capacity test of the lithium full battery was carried out at room temperature with a rate of 0.5 C and a cut-off voltage range of 2.5-4.2 V. The test results are shown in Figure 18-20 As shown; from Figure 18-20 It can be seen that after 160 cycles of the A-P (AN-VAC) full battery of Example 1, it remains at 143 mAh / g; while the specific capacity of the PAN full battery fluctuates slightly at 60 cycles, only 50 mAh / g; the specific capacity of the P (AN-VAC) full battery fluctuates greatly after 120 cycles; In summary, the electrochemical performance of AP (AN-VAC) 1 is relatively stable compared with PAN and P (AN-VAC).
[0069] Experimental detection of Example 8 and Comparative Examples 1 and 2: A half-cell was assembled using AP(AN-VAC)8 membrane, PAN membrane and P(AN-VAC) membrane as electrolyte, lithium sheet as negative electrode and lithium iron phosphate coating as positive electrode. Then the half-cell rate performance test was carried out. The charge and discharge cycles were carried out at current densities of 0.2 C, 0.5 C, 1 C, 2 C, 3 C and 0.2 C respectively. The test cut-off voltage was 2.5-4.2V. Five charge and discharge cycles were carried out at each rate. The results are shown in the figure. Fig.11 ,12,21 as shown.
[0070] from Fig.11 ,12,21It can be seen that the half-cell can be stably charged and discharged at different current densities, and the specific capacity values at the beginning and the end when it returns to 0.2 C are similar, indicating that the electrochemical properties of AP(AN-VAC)8 are stable. At the maximum current density of 3C, the specific capacity reaches 79.1 mAh / g; while the specific capacity corresponding to PAN and P(AN-VAC) fluctuates greatly with the change of current density; but compared with AP(AN-VAC)1, its specific capacity retention rate is not as good as AP(AN-VAC)1.
[0071] Experimental detection of Example 9 and Comparative Examples 1 and 2: A half-cell was assembled using AP(AN-VAC)9 membrane, PAN membrane and P(AN-VAC) membrane as electrolyte, lithium sheet as negative electrode and lithium iron phosphate coating as positive electrode. Then the half-cell rate performance test was carried out. The charge and discharge cycles were carried out at current densities of 0.2 C, 0.5 C, 1 C, 2 C, 3 C and 0.2 C respectively. The cut-off voltage of the test was 2.5-4.2V. Five charge and discharge cycles were carried out at each rate. The results are shown in the figure. Fig.11 ,12,22 as shown.
[0072] from Fig.11 ,12,22It can be seen that the half-cell can be stably charged and discharged at different current densities, and the specific capacity values at the beginning and the end when it returns to 0.2 C are similar, indicating that the electrochemical properties of AP(AN-VAC)9 are stable. At the maximum current density of 3C, the specific capacity reaches 76.5 mAh / g; while the specific capacity corresponding to PAN and P(AN-VAC) fluctuates greatly with the change of current density; but compared with AP(AN-VAC)1, its specific capacity retention rate is not as good as AP(AN-VAC)1.
[0073] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a flame-retardant polymer electrolyte for a lithium-ion battery, characterized in that: The steps of the preparation method are as follows: (1) dissolving acrylonitrile and vinyl acetate in deionized water to obtain solution A, and adding sodium dodecyl sulfate and potassium persulfate to the solution A under a nitrogen atmosphere to obtain solution B; (2) soaking the solution B in a diethylenetriamine solution to obtain a solution C; (3) Filtering the solution C, washing, and drying to obtain product D; (4) adding bacterial cellulose and lithium bis(trifluoromethanesulfonyl)imide to the product D, and dissolving the product D in N-methylpyrrolidone to obtain a solution E; (5) The solution E is poured into a mold, and the solvent is evaporated by heating to obtain a flame retardant polymer electrolyte AP (AN-VAC). The reaction formula of the flame retardant polymer electrolyte is as follows: 。 2. The preparation method according to claim 1, characterized in that: The specific process of step (1) corresponding to each 8-10 g of acrylonitrile is as follows: 8-10 g of acrylonitrile and 1-1.5 g of vinyl acetate are dissolved in 30-35 mL of deionized water to obtain solution A; 0.2-0.3 g of sodium dodecyl sulfate and 0.3-0.4 g of potassium persulfate are slowly added to solution A under nitrogen conditions to obtain a homogeneous solution B.
3. The preparation method according to claim 2, characterized in that: The specific steps of step (2) are: soaking the homogeneous solution B in 40-50 mL of diethylenetriamine solution under a nitrogen atmosphere to obtain solution C.
4. The preparation method according to claim 3, characterized in that: The specific steps of step (3) are: after filtering the solution C, washing it with deionized water and ethanol in sequence to obtain a white solid product; after heating and drying the white solid product, a product D is obtained, and the heating temperature is 60-80°C.
5. The preparation method according to claim 4, characterized in that: The specific steps of step (4) are as follows: 1-1.2 g of product D, 3-4 g of bacterial cellulose with a mass concentration of 0.4% and 0.3-0.32 g of lithium bis(trifluoromethanesulfonyl)imide are mixed and dissolved in 12-15 ml of N-methylpyrrolidone to obtain solution E.
6. The preparation method according to claim 5, characterized in that: The solution E was poured onto a polytetrafluoroethylene template and heated at 60-80° C. for 5-7 h to obtain a flame retardant polymer electrolyte AP (AN-VAC).
7. The preparation method according to claim 6, characterized in that: In the step (1), the concentration of acrylonitrile is 95-99% w / v, and the concentration of vinyl acetate is 95-99% w / v; in the step (2), the concentration of N-methylpyrrolidone is 95-99% w / v.
8. A flame retardant polymer electrolyte for a lithium ion battery, characterized in that: The flame-retardant polymer electrolyte is prepared by the preparation method described in claim 7.
9. A method for preparing a lithium ion battery containing a flame retardant polymer electrolyte, characterized in that: The lithium-ion battery includes a lithium half-cell or a lithium full-cell; The lithium half-cell preparation method comprises the following steps: (A) lithium iron phosphate: carbon black: polyvinylidene fluoride are dispersed in a ratio of 8:1:1 using N-methylpyrrolidone, ground evenly, and then coated on aluminum foil using a scraper, and dried to obtain a lithium iron phosphate electrode; (B) A lithium battery is prepared using a metal lithium sheet as the negative electrode, a lithium iron phosphate sheet as the positive electrode, and AP (AN-VAC) as a polymer flame-retardant electrolyte; The lithium full battery preparation method comprises the following steps: (a) lithium iron phosphate: carbon black: polyvinylidene fluoride are dispersed in a ratio of 8:1:1 using N-methylpyrrolidone, ground evenly, and then coated on aluminum foil using a scraper, and dried to obtain a lithium iron phosphate electrode; (b) artificial graphite: carbon black: polyvinylidene fluoride is dispersed in N-methylpyrrolidone in a ratio of 8:1:1, ground evenly, coated on aluminum foil with a scraper, and dried to obtain a graphite electrode; (c) A lithium battery was prepared using graphite as the negative electrode, lithium iron phosphate as the positive electrode, and AP (AN-VAC) as a polymer flame-retardant electrolyte; The AP (AN-VAC) is prepared by the preparation method described in claim 7.
10. A lithium ion battery containing a flame retardant polymer electrolyte, characterized in that: The lithium-ion battery is prepared by the preparation method described in claim 9.
Citation Information
Patent Citations
Double-layer solid electrolyte composite membrane mainly composed of polyacrylonitrile and preparation method and application thereof
CN109524719A
Lithium ion conductive composite material for all solid-state lithium battery, and solid polymer electrolyte and all solid-state lithium battery including the same
CN112490498A
Preparation method and application of PC-PAN-based composite solid electrolyte membrane
CN116914238A
Gel polymer electrolytes comprising electrolyte additive
US20190140317A1
Elastomer / Inorganic Hybrid Solid-State Electrolytes, Lithium Batteries Containing Same, and Production Processes
US20230238575A1